OP0028 Efficacy and safety of bcd-085, a novel il-17 inhibitor, in ankylosing spondylitis. results of phase 2 clinical study. (12th June 2018) - Mazurov, V.; Erdes, S.; Kunder, E.; Soroka, N.; Shesternya, P.; Smakotina, S.; Raskina, T.; Krechikova, D.; Dubinina, T.; Eremeeva, A.; Dokukina, E.; Chernyaeva, E.; et al.
Abstract : Background: BCD-085 is an innovative humanised monoclonal antibody against interleukin-17 with genetically modified Fc- and CDR-regions, aimed to improve treatment outcomes in patients with several autoimmune disorders. Objectives: This abstract presents the results of double-blind placebo controlled dose-finding phase II clinical study of efficacy and safety of subcutaneous BCD-085 in patients with ankylosing spondylitis. Methods: The study was conducted as international multicenter randomised double-blind placebo controlled study. The study enrolled 88 adults with active AS. Patients were randomised in 4 study arms in 1:1:1:1 ratio to receive 40, 80 or 120 mg of BCD-085 or placebo. In the active period of the study, patients received the test drug/placebo SC injections once weekly for the first three weeks of treatment and then every other week till Wk 12. After Wk 12 all patients underwent follow-up for 4 weeks. Results: Efficacy: BCD-085 is superior to placebo in doses 80 and 120 mg. ASAS20 at wk 16 was reached by 81.82%, 90.91% and 42.86% of patients in BCD-085 80 mg, 120 mg and placebo arm respectively (p=0.008, 95% CI for difference in proportion [12.36%; 65.56%]; p=0.001, 95% CI: 23.71% to 72.39%], superiority margin 10%). Significant reduction of AS activity was revealed for all BCD-085 arms: by Wk 4 BASDAI and ASDAS-CRP scores decreased and maintained achieved levels till the end of the study. Other secondary endpoints (ASAS40, ASAS5/6, BASMI, BASFI, BASDAI, MASES, chest expansion, QoL, spinal pain) had the corresponding dynamics: by the time of second evaluation (Wk 1 for spinal pain, Wk 4 for other endpoints) significant improvement with no further negative changes was revealed. For all evaluated endpoints the most pronounced response was established for BCD-085 120 mg arm. In placebo arm no significant dynamics was shown. Safety: All arms had highly similar safety profiles. Most of AEs were presented as mild or moderate laboratory abnormalities (ANC decreased, WBC increased) and moderate arterial hypertension. The rates of AEs were equivalent for all BCD-085 doses and placebo. There were no cases of SAEs, treatment discontinuation due to safety reasons or local reactions. Immunogenicity assessment did not detect formation of binding antibodies. Conclusions: Treatment with BCD-085 leads to significant improvement in all AS symptoms in comparison with placebo. The dose of 120 mg of BCD-085 had the most pronounced effect. The drug was well tolerated in all doses with no differences with placebo in safety profiles. Disclosure of Interest: V. Mazurov: None declared, S. Erdes: None declared, E. Kunder: None declared, N. Soroka: None declared, P. Shesternya: None declared, S. Smakotina: None declared, T. Raskina: None declared, D. Krechikova : None declared, T. Dubinina: None declared, A. Eremeeva Employee of: JSC BIOCAD, E. Dokukina Employee of: JSC BIOCAD, E. Chernyaeva Employee of: JSC BIOCAD, R. Ivanov Employee of: JSC BIOCAD